Promotion of hydrogenation activity and sulfur resistance over Ni/ASA catalyst by support modification simultaneously with P and USY. Issue 66 (25th August 2017) - Cui, Sha; Ge, Jiaqi; Wang, Genggeng; Yang, Ying; Liu, Baijun
Abstract : Compared to Ni/ASA (Cat), individual and simultaneous P and USY promoted ASA supported Ni catalysts display higher naphthalene hydrogenation activity, especially the simultaneous P and USY promoted catalyst. Abstract : Individual and simultaneous P and USY promoted amorphous SiO2 –Al2 O3 (ASA) supported Ni catalysts were prepared using the hydrothermal synthesis method with the assistance of cis -9-octadecenylamine. The catalysts were characterized by X-ray diffraction (XRD), N2 -adsorption and desorption, UV-vis diffuse reflectance spectroscopy, FTIR spectroscopy of adsorbed pyridine (Py-IR), transmission electron microscopy (TEM), temperature-programmed hydrogen reduction (H2 -TPR) and X-ray photoelectron spectroscopy (XPS). The effects of P and USY loading on the activity of naphthalene hydrogenation were evaluated in a fixed bed reactor under the following reaction conditions: P = 4 MPa, GHSV = 16 h −1, H2 /oil = 600 volume ratio, T = 200, 240, 280 and 320 °C. Experimental results verified that all individual P and USY modified catalysts displayed higher hydrogenation activity than the freely P and USY decorated catalyst at 200–280 °C. Furthermore, the catalyst simultaneously modified with 1.0 wt% P and 10 wt% USY had the highest hydrogenation activity and sulfur tolerance. Multiple effects, such as metal dispersion, acid amount, surface exposure of the active Ni° species and the [NiOh 2+ ]/[NiTd 2+ ] ratio were responsible for the high hydrogenation activity of P and USY-promoted catalysts.